2005
DOI: 10.1246/cl.2005.814
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradative Surfactants: p-Dodecylbenzyltrimethylammonium Bromide as a Photodegradative Emulsifier for Microemulsion Polymerization

Abstract: A photodegradative surfactant, p-dodecylbenzyltrimethylammonium bromide, was used as an emulsifier for micro-emulsion polymerization of methyl methacrylate in water. The resulting polymer latex was coagulated during UV irradiation. The analysis of the centrifuged solid after irradiation indicated almost perfection of both recovery of the polymer and removal of surface-active species from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Several types of cleavable surfactants including photodegradable4–6 and hydrolysable7–9 ones have been applied to coagulate latices and decrease the surfactant content in the resulting polymers. We have recently demonstrated that an UV‐degradable surfactant, ( p ‐dodecylbenzyl)trimethylammonium bromide, can be used not only as an emulsifier for microemulsion polymerization of methyl methacrylate but also as an useful “flocculant” of latices that gives surfactant‐free polymers 10. This system, however, has two drawbacks: (1) complete photolysis (i.e., conversion to a nonsurfactant) appears to be slow: it takes more than 60 min under a given condition, (2) opaque latex solutions will be inapplicable.…”
Section: Introductionmentioning
confidence: 99%
“…Several types of cleavable surfactants including photodegradable4–6 and hydrolysable7–9 ones have been applied to coagulate latices and decrease the surfactant content in the resulting polymers. We have recently demonstrated that an UV‐degradable surfactant, ( p ‐dodecylbenzyl)trimethylammonium bromide, can be used not only as an emulsifier for microemulsion polymerization of methyl methacrylate but also as an useful “flocculant” of latices that gives surfactant‐free polymers 10. This system, however, has two drawbacks: (1) complete photolysis (i.e., conversion to a nonsurfactant) appears to be slow: it takes more than 60 min under a given condition, (2) opaque latex solutions will be inapplicable.…”
Section: Introductionmentioning
confidence: 99%
“…Work is in progress in our laboratory to improve the efficiency of photodegradation as well as to apply those in the fields of separation technology. 21…”
Section: Discussionmentioning
confidence: 99%
“…[6] This surfactant has been also used as a photocleavable emulsifier for microemulsion polymerization which gives surfactant-free polymers. [7] We also emphasize that this type of surfactants are stable under usual conditions (e.g., stable to solar irradiation and non-hydrolysable in acidic and basic solutions) and are surface-active as good as commercially available cationic surfactants. [6,8] Here we report the surface-active and photochemical properties of a novel anionic surfactant, sodium p-dodecylbenzylsulfate (C 12 BS), which is expected to be an alternative to one of the most commercially available and the most important synthetic detergents, linear alkylbenzenesulfonate (LAS).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, our preliminary experiment 7 showed that C 12 BS, as well as C 12 BA, [7] can be used as a photocleavable emulsifier for microemulsion polymerization of methyl methacrylate in water, which gives surfactant-free polymers. These facts exemplify the usability of C 12 BS in separation and purification technologies.…”
Section: Photolysismentioning
confidence: 98%